The management of colorectal liver metastases. Issue 8 (August 2017) - Maher, B.; Ryan, E.; Little, M.; Boardman, P.; Stedman, B.
Abstract : Colorectal cancer remains a leading cause of cancer-related death in Europe. Approximately one-quarter of patients have synchronous hepatic metastases and metachronous liver metastases occur in a further 30%. The scope of surgery in management of colorectal metastases has evolved to include selected patients with extra-hepatic disease for whom R0 resection is considered feasible; however, locoregional treatments are increasingly recognised as viable management options in those patients deemed unsuitable for surgery and there is an expanding body of evidence regarding their ability to achieve local control and increase progression-free survival in the liver. Locoregional therapies increasingly practised in the management of unresectable liver metastatic colorectal cancer (mCRC) include percutaneous ablation, primarily in the form of radiofrequency ablation or microwave ablation, although there remains a lack of data regarding long-term outcome. Radio-embolisation (RE) is the most comprehensively studied embolisation technique in the context of colorectal liver metastases, predominantly using yttrium 90 ( 90 Y). The data published to date suggests that 90 Y represents a safe and effective cytoreductive modality. The optimal dose and timing of therapies remains uncertain and further studies are required to determine its relationship with systemic treatment. Irinotecan-loaded drug-eluting beads (DEBIRI) transcatheter arterial chemo-embolisation (TACE) represents a further therapy with considerable potential. There is evidence of improved overall survival in the salvage setting. As with the other therapies discussed, further research is required to elucidate the optimal role and timing of these treatments within the increasingly crowded space of therapies for mCRC.